2014
DOI: 10.1155/2014/763494
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiadipogenic Activities of Galkeun‐Tang, a Traditional Korean Herbal Formula

Abstract: Galkeun-tang (GKT; Galgen-tang in Chinese and Kakkon-to in Japanese), a traditional herbal formula, has been used for treatment of the common cold. Here, we report in vitro antioxidant and antiadipogenic effects of GKT. GKT increased the activities of scavenging 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. GKT also significantly reduced the malondialdehyde (MDA) generation during low-density lipoprotein (LDL) oxidation and the electrophoretic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…GGWE is a traditional herbal decoction that has been used to treat common cold, fevers, and inflammatory diseases in China, Japan, and Korea [ 10 , 23 ]. Experimental studies have revealed that GGWE has anti-viral, anti-allergic, antioxidant, and antiadipogenic effects [ 13 , 14 , 15 , 24 , 25 ]. Furthermore, GGWE was shown to reduce inflammatory mediators such as inflammatory cytokines, iNOS, and NF-κB expression through the inhibition of NF-κB in LPS-stimulated microglial cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…GGWE is a traditional herbal decoction that has been used to treat common cold, fevers, and inflammatory diseases in China, Japan, and Korea [ 10 , 23 ]. Experimental studies have revealed that GGWE has anti-viral, anti-allergic, antioxidant, and antiadipogenic effects [ 13 , 14 , 15 , 24 , 25 ]. Furthermore, GGWE was shown to reduce inflammatory mediators such as inflammatory cytokines, iNOS, and NF-κB expression through the inhibition of NF-κB in LPS-stimulated microglial cells [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from other groups have also shown that IRAK1 inhibitors such as 2-hydroxy-5,6-dihydroisoindolo[1,2-a]isoquinoline-3,8-dione, mangiferin, and corosolic acid and the mixture of the rhizomes of Anemarrhena asphodeloides and Coptidis chinensis exhibit anti-inflammatory activities when applied to in vivo endotoxemia and colitis animal models [25, 32, 40, 41]. Together, these results strongly suggest that IRAK1 positively regulates numerous inflammatory diseases and therefore has significant potential to be targeted in order to treat a broad range of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, antioxidant therapy is considered as an attractive approach to treat various human diseases [ 34 , 35 ]. To date, previous studies reported significant antioxidant activities of various herbal formulas such Galkeun-tang [ 36 ] and Samchulgeonbi-tang [ 37 ] by regulating the free radical scavenging activity were reported. The current study data revealed that UGS extract activate the free radical scavenging effects against ABTS and DPPH.…”
Section: Discussionmentioning
confidence: 99%
“…The ABTS radical-scavenging activity of the UGS extract was assessed according to the previous study [ 36 ]. The ABTS radical cation was prepared by reaction with a 7 mM ABTS solution and 2.45 mM potassium persulfate, followed by keeping in the dark at room temperature for 16 h. The absorbance of the reaction mixture was adjusted to 0.7 at 734 nm.…”
Section: Methodsmentioning
confidence: 99%